Pengaruh Volume Bongkar Dan Muat Barang Terhadap Volume Pendapatan Perusahaan PT. Varuna Tirta Prakasya (PERSERO) Di Pelabuhan Benoa Kabupaten Badung - Ni Ketut Murdani; Anak Agung Elik Astari (Universitas Mahendradatta Denpasar, 2019)
KMP Nusa Jaya Abadi is primarily intended to connect the economic artery of Klungkung district in general and the island of Bali and small islands in Nusa Penida in particular. Since inaugurated its operation by the President of RI in 2007 until now the revenue from the port and shipping sectors served by Motor Vessel Penyebrangan Roro Nusa Jaya Abadi has reached more than 3.2 billion rupiah which consists of operational unit of loading and unloading goods and port charges.The purpose of this study is to know the analysis of loading and unloading of goods in increasing the Local Original Revenue (PAD) in the Port of Nusa Penida Distribution Klungkung regency.This research was conducted on Technical Implementation Unit of Port of Penpenangan Nusa Penida of Klungkung Regency. While the object of this research is the operational implementation of loading and unloading ship ports in an effort to increase local revenue (PAD).Data collection techniques include observation, interviews, and document recording. The method used in this research is quantitative analysis: correlation analysis, determination analysis, and t-test analysis.The results obtained from this research are: correlation analysis obtained correlation value (r) of = 0.9957, this means that the relationship between the independent variables of loading and unloading with the dependent variable Original Revenue has a correlation coefficient of 0.9957.From result of calculation of determination obtained result equal to 99,15%. This means that loading and unloading activities have an effect on increasing the original income of 99.15%, while the remaining 0.85% is the influence of other variables that are not measured in this study.While the results of t-test analysis obtained value of 10.7792 or (10.7792 6.3140), it can be said that the relationship that occurs between loading and unloading activities with the original revenue is significant (meaningful).